Description of a new genus and species of Pseudothelphusidae Ortmann, 1893 (Decapoda: Brachyura) from Panama, and new records and remarks on the zoogeography of Trichodactylus quinquedentatus Rathbun, 1893 (Trichodactylidae) in Central America. Issue 1 (7th January 2019) - Magalhães, Célio; Ng, Peter K L
ABSTRACT: A collection of freshwater crabs from Central America resulted in the description of a new genus and two new species of pseudothelphusid crabs from Panama, and the record of the trichodactylid Trichodactylus quinquedentatus Rathbun, 1893 from Honduras and Panama. A new monotypic genus, Emberacarcinus n. gen., is erected to accommodate Potamocarcinus darienensis Magalhães, Campos & Türkay, 2013 . The two new species and can be distinguished from their respective congeners by the structures of the male first gonopods: Ptychophallus bilobatus n. sp. has a bilobed mesial process whereas Potamocarcinus tapirrhynchus n. sp. exhibits a mesial process as a stout, rounded projection obliquely directed apical-cephalically and partially fused to the mesial lobe of the apical crest. The taxonomic affinities of both species with their closest congeners are treated, and the zoogeographic implication of the new records of T. quinquedentatus in Central America is discussed.